1999
DOI: 10.4141/p98-008
|View full text |Cite
|
Sign up to set email alerts
|

No-till alfalfa stand termination strategies: Alfalfa control and wheat and barley production

Abstract: alfalfa stand termination strategies: Alfalfa control and wheat and barley production. Can. J. Plant Sci. 79: 71-83. Crop rotations involving perennial alfalfa (Medicago sativa L.) present the unique problem of terminating the alfalfa stand. Intensive tillage currently used to terminate alfalfa increases the risk of soil erosion and reduces many of the rotational benefits from alfalfa. Inadequate alfalfa termination results in severe competition to the following crop by surviving alfalfa plants. Field experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…A preharvest application of glyphosate is registered for forage alfalfa just before the final cut in the termination year. When used in this manner, glyphosate kills alfalfa plants and facilitates crop rotation (Bullied et al 1999). On the other hand, there is evidence to suggest that glyphosate application during the reproductive stage of alfalfa can be much less injurious with a 22-33% stand reduction at 800 g a.i.…”
mentioning
confidence: 98%
“…A preharvest application of glyphosate is registered for forage alfalfa just before the final cut in the termination year. When used in this manner, glyphosate kills alfalfa plants and facilitates crop rotation (Bullied et al 1999). On the other hand, there is evidence to suggest that glyphosate application during the reproductive stage of alfalfa can be much less injurious with a 22-33% stand reduction at 800 g a.i.…”
mentioning
confidence: 98%
“…Yields of crops sown after alfalfa may or may not be affected by stand termination technique. Bullied et al (1999) observed similar yields with tilled and no-till systems, provided that complete alfalfa suppression was achieved. Higher crop WUE under no-till (Lafond et Abbreviations: WUE, water use efficiency.…”
mentioning
confidence: 58%
“…Capturing and storing fall and overwinter precipitation is especially important in alfalfa systems, where soil often is drier (Campbell et al, 1990). Effective herbicide termination systems are available for alfalfa (e.g., Bullied et al, 1999); however, only those that leave 15 to 20 em of standing crop residue on the surface would be expected to trap significant amounts of snow (de Jong and Steppuhn, 1983). Because including alfalfa in a crop rotation increases soil aggregation (Raimbault and Vyn, 1991) and adds organic matter (Campbell et al, 1990), water infiltration rates and soil water storage capacity may well be higher in alfalfa-containing than in annual crop rotations.…”
mentioning
confidence: 99%
“…Wheat growth and grain yield were suppressed in plots where persisting legume plants occurred. Alfalfa was controlled by applications of clopyralid, glyphosate, and other herbicides before seeding wheat in a subhumid region (Bullied et al, 1999), but these same treatments did not control alfalfa consistently in western North Dakota (Carr, unpublished data, 2004). The efficacy of many herbicides declines when hot and dry conditions develop, as commonly occurs in late summer in much of the northern Great Plains.…”
Section: Discussionmentioning
confidence: 99%